2015
DOI: 10.1002/chem.201503969
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Bridged Polycyclic Systems by Polyene Cyclization

Abstract: A stereoselective construction of bridged tri- and tetracyclic systems embedded in some 3,5-dimethylorsellinic acid (DMOA)-derived meroterpenoids was achieved by exploiting a polyene cyclization of suitably functionalized epoxyallylsilanes. Both the olefinic substituent on the epoxide and allylic trimethylsilyl (TMS) group were found to play pivotal roles in the success of the present reaction. The fact that the cyclization of monocyclized byproducts did not proceed strongly suggests that the reaction could be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 105 publications
0
7
0
Order By: Relevance
“…Pioneering work by Goldsmith and van Tamelen revealed that BF 3 ·Et 2 O catalyzes epoxide-initiated cation–olefin polycyclizations . Corey established that MeAlCl 2 and analogous compounds are efficient catalysts, and they have been used to construct many natural polycyclic terpenoids . Other Lewis acids (e.g., InBr 3 , Sc­(OTf) 3 , SnCl 4 , , FeCl 3 , , TiCl 4 ), zeolites, , and radical catalysts (Ti 3+ ) also catalyze cascade cyclizations.…”
mentioning
confidence: 99%
“…Pioneering work by Goldsmith and van Tamelen revealed that BF 3 ·Et 2 O catalyzes epoxide-initiated cation–olefin polycyclizations . Corey established that MeAlCl 2 and analogous compounds are efficient catalysts, and they have been used to construct many natural polycyclic terpenoids . Other Lewis acids (e.g., InBr 3 , Sc­(OTf) 3 , SnCl 4 , , FeCl 3 , , TiCl 4 ), zeolites, , and radical catalysts (Ti 3+ ) also catalyze cascade cyclizations.…”
mentioning
confidence: 99%
“…While related cyclohexanols have been assembled from geraniol derivatives, we sought an efficient method to incorporate the requisite alkynyl moiety. [24][25][26][27][28][29][30][31][32] To this end, we developed an auxiliary ring strategy wherein bicyclic ketone 11 was used as a synthetic linchpin for the construction of monocyclic alkyne 9 (Figure 1D and Figure 2A). Bicyclic ketone 11 could, in turn, be disconnected to epoxide 12¸ a derivative of geraniol, by a Ti(III)-mediated radical cyclisation.…”
Section: Scheme 1 Total Synthesis Of (±)-Leonuketalmentioning
confidence: 99%
“…While polyene cyclization reactions are often used in the synthesis of fused polycyclic ring systems, their use in the construction of bridged polycyclic ring systems was only recently, in 2015, explored by Nakamura and co-workers (Scheme 4). 9 Exposure of epoxyallylsilane 13 to diethylaluminum chloride resulted in polyene cyclization via carbocation intermediates 14 and 15 to produce bridged tricyclic compound 16 (72%) after hydrolysis. Tetracyclic product 18 (37%) was also obtained under the same conditions from epoxyallylsilane 17.…”
Section: Scheme 3 Synthesis Of (+)-Dixiamycin Bmentioning
confidence: 99%